2019
DOI: 10.1111/tpj.14547
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of ZAR1 immune receptor reveals key molecular interactions for activity

Abstract: Summary NLR (nucleotide‐binding [NB] leucine‐rich repeat [LRR] receptor) proteins are critical for inducing immune responses in response to pathogen proteins, and must be tightly modulated to prevent spurious activation in the absence of a pathogen. The ZAR1 NLR recognizes diverse effector proteins from Pseudomonas syringae, including HopZ1a, and Xanthomonas species. Receptor‐like cytoplasmic kinases (RLCKs) such as ZED1, interact with ZAR1 and provide specificity for different effector proteins, such as HopZ1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 105 publications
2
26
0
Order By: Relevance
“…To validate the ZAR1 constructs we generated, we first used agroinfiltration to transiently express wild-type ZAR1 and the MHD mutants AtZAR1 D489V and NbZAR1 D481V in N. benthamiana leaves ( Figure 2A). As recently reported by Baudin et al (2019), AtZAR1 did not trigger macroscopic cell death in N. benthamiana leaves even when the full-length protein carries the D489V mutation in the MHD motif ( Figure 2B and 2C). In contrast, NbZAR1 caused macroscopic cell death when the MHD mutant NbZAR1 D481V was expressed in N. benthamiana leaves ( Figure 2D and 2E).…”
Section: Unlike Arabidopsis Zar1 Nbzar1 Triggers Autoimmune Cell Deasupporting
confidence: 84%
“…To validate the ZAR1 constructs we generated, we first used agroinfiltration to transiently express wild-type ZAR1 and the MHD mutants AtZAR1 D489V and NbZAR1 D481V in N. benthamiana leaves ( Figure 2A). As recently reported by Baudin et al (2019), AtZAR1 did not trigger macroscopic cell death in N. benthamiana leaves even when the full-length protein carries the D489V mutation in the MHD motif ( Figure 2B and 2C). In contrast, NbZAR1 caused macroscopic cell death when the MHD mutant NbZAR1 D481V was expressed in N. benthamiana leaves ( Figure 2D and 2E).…”
Section: Unlike Arabidopsis Zar1 Nbzar1 Triggers Autoimmune Cell Deasupporting
confidence: 84%
“…Similar to TIR domains, the hetero‐ and homo‐dimerization of CC domains of CNLs have also been shown (El Kasmi et al 2017; Bentham et al 2018; Zou et al 2018a; Baudin et al 2019), yet the role of dimerization is not clear. A recent interactome analysis demonstrated that the heterodimerization of CC domains is more frequent than homodimerization, indicating that CNLs may form a network to mediate immune responses after the perception of effectors.…”
Section: Recent Discoveries Of the Activation Of Intracellular Nlrsmentioning
confidence: 99%
“…Effector detection often occurs (directly or indirectly) at the C‐terminal LRR domain, and results in the exchange of ADP for ATP in the NBARC domain due to deep conformational reorganization of NLR domains. In many cases, oligomerization of the N‐terminal domain (CC or TIR) is associated with the activation of the NLR and the induction of downstream signalling (Baudin, Hassan, Schreiber, & Lewis, 2017; Baudin, Schreiber, Martin, Petrescu, & Lewis, 2019; Bernoux et al, 2011; Maekawa et al, 2011). The mechanisms by which activated NLRs induce defence responses remain elusive as very few signalling pathways have been identified so far.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that protein domains of ZAR1 are involved in specific intra‐ and inter‐molecular interactions that are critical for ZAR1 activity and prevent inappropriate activation of the NLR (Baudin et al, 2017, 2019; Liu et al, 2019). The LRR domain of ZAR1 is important for interactions with ZED1, RKS1/ZRK1 and ZRK3 (Baudin et al, 2017; G. Wang, Roux, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%